A responsabilidade civil das instituições financeiras pelos danos ambientais causados pelos tomadores de crédito - AVELINO, Daniel César Azeredo (Universidade Federal do Pará, 2017)
The protection on the environment is a fundamental right for the Brazilian constitutional order, which even protects the future generations by its provisions. However, although clear as it may seam, the effective protection of the environment encounters concrete obstacles regarding the difficulty in implementing the constitutional text in complex private activities, typical of the modern period. In this context, financial institutions have taken a unique role and importance in the various relationships that operate between man and the environment in the absence of a codified regulation that would clearly and systematically present the requirements and cautions that banks should obey to while funding a certain project. Faced with this scenario, the present study attempts to compile the various constitutional, legal and infra-legal rules on the subject, in order to, afterwards, carry out an investigative field research, by sampling, to investigate the degree of compliance by the financial institutes to the existing rules. Furthermore, theses rules are critically analyzed, searching, in a constitutional level, for robust theoretical framework that demonstrates the civil liability of the financial institutions for environmental damage caused by its customers, more broadly, from the analysis of each case. This is an essential step to the research, given the simplicity of the infra-legal specific rules on the subject, which end up leaving the constitutional protection at a significant risk. In this process of doctrinal construction, we seek the exact understanding of the historical evolution of key institutions, such as contracts and property, as well as a detailed analysis of the application of fundamental rights in private relations.